Epigenetic Understanding of Gene-Environment Interaction in Autism Spectrum Disorder - Kubota, Takeo (Journal of Pediatric Neurology, 2017)
The number of children with autism spectrum disorder (ASD) has increased in many countries over the past 10 years. Genetic studies have revealed that ASD is caused by mutations in the genes coding proteins related to neuronal function. However, such genetic abnormalities cannot underlie the increase in this disorder since mutations do not accumulate among children in the short-term. Epigenetics is a mechanism that is involved in gene regulation not by changing DNA sequence (mutations) but by changing the chemical modifications of DNA and histone proteins. Current studies suggest that mental stress and other forms of environmental stress in early life alter the epigenetic status of genes and change the neuronal gene function, resulting in persistent behavioral abnormalities. Therefore, it can be speculated that the current increase in the prevalence of ASD is partially caused by epigenetic changes in the brains of children induced by some recent socio-environmental conditions. However, epigenetic changes are reversible. Indeed, it has been demonstrated that some drugs for mental disorders reverse the altered epigenetic state and recover the expression of neuronal genes. It has also been demonstrated that offering an appropriate nurturing environment in early life reverses the altered epigenetic state and recovers the neurological gene function in mouse models of ASD. Therefore, from the epigenetic point of view, early medical and educational interventions may be important for children with ASD.
Keywords: autism; spectrum disorder; gene; epigenetics; environmental stress; early intervention